Penelitian Terapan Ekonometrika Dalam Sistem Informasi Akuntansi Permodelan Time Series Data Penjualan Jasa Salon Kendaraan Bermotor X Dengan Metode Arima Untuk Meningkatkan Kualitas Informasi Kinerja Divisi Penjualan - Bonnie Soeherman (AKRUAL: JURNAL AKUNTANSI, 2013)
AbstractInformation is an absolute fuel to trigger the decision making process. Information failure can be fatal and impact on the future. The concept of accounting information system offered an alternative of how to design systems to produce effective information in efficient way. Historical financial accounting information was not adequate as a basis for strategic decision making. Accounting information should been complemented with information that has future orientation or predictive value. Therefore, this study tried to give new thought to minimize the gap in accounting information and decision-making through econometric or statistical techniques with pilot projects sold data modeling time series with ARIMA method. This research was applied and more emphased on aspects of practical value to the world than to enrich the theory by simply disassembling the variables. I found that future oriented-information had better strategic value for decision making process.